EFEKTIFITAS PEMBIAYAAN SEKTOR AGRIBISNIS DALAM MENINGKATKAN PENDAPATAN PETANI DI KECAMATAN SELO KABUPATEN BOYOLALI - Prasetyo, Analis Yusuf; Supriyanto, Supriyanto (Faculty of Islamic Economics and Business, Sultan Aji Muhammad Idris State Islamic University of Samarinda, 2022)
This study aims to identify financing opportunities and obstacles in the agribusiness sector in Boyolali District as well as the effectiveness of agribusiness financing provided by financial institutions on farmers' income. This study used a qualitative method supported by quantitative data. This study used both primary data and secondary data. Data were collected through interviews and documentation. The data were tested for validity using the triangulation technique. Then, the data were also crossed check. The results of this study showed that in carrying out the agribusiness financing, Bank Jateng Syariah faced the following obstacles, namely 1) the agribusiness sector is a risky business sector, 2) the length of time in the agribusiness sector, 3) the agribusiness sector requires large input costs, and 4) Lack of qualified human resources. The effectiveness of agribusiness financing is seen from some aspects. The first is usefulness. Islamic Banks provide capital to meet the short-term production needs of food and non-food crops. The second aspect is accuracy and objectivity. Problems with access to agricultural credit and banks’ low interest are caused by non-well targeted credit. The third aspect is scope. Distributing agribusiness financing face many obstacles. The fourth aspect is cost-effectiveness. Farmers lack knowledge of Islamic banking due to the location of the bank which is far. The fifth aspect is accountability. Based on the total financing in Islamic banks in 2019-2021, financing in the agribusiness sector continues to increase. The last aspect is punctuality. In terms of payment of financing in the agribusiness sector, everything went smoothly and with no problems. The distribution of agribusiness financing by Bank Jateng Syariah is less effective as it is still below 2%. However, the percentage increases each year and can be said to be effective as the total agribusiness financing increases each year too. In terms of the effectiveness of agribusiness financing in increasing farmers' income in Selo Sub-district, Boyolali District, it can be said to be effective. The income proposed by the procurement of goods and production facilities increased compared to the previous income of 50%. Then, income from the farming business also increases compared to the previous income of 36%. Meanwhile, the income proposed by Processing increases from the previous income of 50% and the income proposed by Marketing also increases from the previous income of 15%.